Inclusive marketing and its impact on brand image in cosmetics industry - Tůmová, Kateřina; Escobar Rios, Andrea; Martínez Pantoja, Yadira Ixchel; Vysoká škola ekonomická v Praze. Fakulta mezinárodních vztahů (2024)
Inclusive marketing has gained its significance in the recent years as many consumers have started to pay more attention to the advertising content of brands. This thesis aims to describe the impact of inclusive marketing on brand image within cosmetics industry in the Czech Republic as there has not been conducted sufficient research on the Czech market. The theoretical framework discusses the concepts based on existing literature. The practical part describes the methodology and presents the data obtained from the primary quantitative research. The findings are discussed in terms of consumers' awareness, perception, expectations and attitude as well as potential implications for brands. Moreover, thesis limitations and suggestions for further research are included at the end.
Vedoucí práce: Andrea Escobar Rios
Bakalářská práce (Bc.)—Vysoká škola ekonomická v Praze. Fakulta mezinárodních vztahů, 2025
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2025
Způsob přístupu: Internet
Keywords: mezinárodní obchod [obor bakal. práce]; bakalářské práce; bachelor's theses